Special characteristics of spare - Kalev, Krasimir (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Some aspects in the problem of management inventory system for spare elements are presented in this paper. The life cycle management of spare elements and their special characteristics is considered in the inventory process. The machine time-down divided with partial weighing range is shown. Emphasis is on the delivery time of spare elements, as the main reason for a fast repair of the failing machine. It’s therefore necessary to predict the demand for spare elements.